Perceptions of risk allocation methods and equitable risk distribution: a study of medium to large Southeast Queensland commercial construction projects. Issue 2 (3rd April 2017) - Perez, David; Gray, Jason; Skitmore, Martin
Abstract : Economic upheaval and project complexity often lead to unequal risk allocation between contractual parties. A review of the literature identifies major problems in relation to the fairness and equality of the risk allocation process. However, most existing studies have been conducted from the client's perspective rather than that of contractors or consultants and do not focus specifically on risk misallocation. This paper aims at determining the factors involved by a questionnaire survey of the perceptions of contractors and consultants of the main issues in relation to medium to large commercial construction projects in South East Queensland, Australia. The findings are generally consistent with existing research results in that approximately half the respondents feel that their contractual risk allocation is unfair. In addition, there is a lack of use of formal risk management methods, and the arbitrary passing down of risks from the client has increased in recent years. A better understanding is provided of the issues contributing to unequal risk allocation, decision-making and management that will help promote fairness and equality between the contractual parties in the current process of risk management.